Oral health condition of leukemic patients in PGH (Dec 1994 - Jan 1995) - Echiverry, Vicki-Mari L.
As a consequence of leukemia, patients are prone to infections which may lead to morbidity and mortality. The oral cavity, being a nidus of microorganisms, is a possible source of infection. This study was conducted to emphasize the need for dental consultation prior to and during chemotherapy. Leukemia patients admitted in wards 9 and 11 of PGH were examined intraorally by visual inspection. Results show that all soft tissues were normal in majority of the patients except for the gingivae, which showed carying degrees of swelling. Other oral manifestations were gingival hemorrhage, marginal erythema, hyperplastic gingiva, and candidal infection. Plaque accumulation and significant number of non-restorable carious teeth were noted. The results underline a need for the dental management of oral problems among the leukemic patients.